CONCEPTO ACTUAL DEL INTERÉS SUPERIOR DE LA NIÑEZ EN LA LEGISLACIÓN MEXICANA - Santana Campas, Marco Antonio (UNIVERSIDAD DE SONORA, 2021)
When talking about the PISN (principle of the best interests of childhood), it can be perceived that it refers to the care and needs that people under 18 years of age have, due to their lack of maturity and their state of natural vulnerability, The same that causes not having legal capacity to carry out legal acts, which is why at the international level the principle of the best interests of children was created, which in Mexico is established in the CPEUM (Political Constitution of the United Mexican States ) and extends to the laws and regulations of this country, in order to provide protection to children in whatever their situation, however, this principle is not clear